2007
DOI: 10.1182/blood-2006-12-061689
|View full text |Cite
|
Sign up to set email alerts
|

Antimetabolite therapy for lesser-risk B-lineage acute lymphoblastic leukemia of childhood: a report from Children's Oncology Group Study P9201

Abstract: Pediatric Oncology Group (POG) protocol 9201 enrolled children with lesser-risk Blineage acute lymphoblastic leukemia (ALL) defined by age (1-9), white blood cell count (WBC) less than 50 ؋ 10 9 /L (50 000/L), DNA findings of trisomies 4 and 10 (or DNA index > 1.16), and lack of overt central nervous system (CNS) leukemia. After vincristine, prednisone, and asparaginase induction, 650 of 653 eligible patients attained remission (3 induction deaths) and received 6 courses of intravenous methotrexate (1 g/m 2 ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 55 publications
(67 reference statements)
2
32
0
1
Order By: Relevance
“…Contrary to the recent practice of some cooperative groups, the CNS-2 cohort did not receive additional doses of IT chemotherapy during induction on this study. 67,69,70 Interestingly, ITT reduced the iCNS relapse rate 5-fold compared with IT MTX in the CNS-2 subset. Excess BM relapses and poorer EFS did not occur in the CNS-2 cohort treated with ITT compared with IT MTX.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the recent practice of some cooperative groups, the CNS-2 cohort did not receive additional doses of IT chemotherapy during induction on this study. 67,69,70 Interestingly, ITT reduced the iCNS relapse rate 5-fold compared with IT MTX in the CNS-2 subset. Excess BM relapses and poorer EFS did not occur in the CNS-2 cohort treated with ITT compared with IT MTX.…”
Section: Discussionmentioning
confidence: 99%
“…62 However, it should be noted that phenotypic shifts or the emergence of a clone that was present only at low levels at the time of diagnosis may occasionally lead to false-negative results. 61 Flow-based MRD detection has been used successfully by investigators from the BFM study group, 63 the COG, 64,65 and St Jude. 9,66 In one of the first studies reported, Sievers et al demonstrated that immunophenotypic evidence of leukemic blasts at the time of morphologic remission was predictive of more rapid relapse.…”
Section: Patientmentioning
confidence: 99%
“…13,14 These patients constituted a subset of all patients who had enrolled on these trials from November 15, 1994 to November 15, 1999. Definitive results regarding TEL status were obtained in 926 patients, who are the subject of this report.…”
Section: Patients and Samplesmentioning
confidence: 99%
“…Vincristine/prednisone pulses were given throughout continuation therapy and triple intrathecal therapy was used for central nervous system prophylaxis. 13 Patients with standard-risk ALL (POG 9605) received the same consolidation therapy as the low risk patients, but were randomly assigned, in a 2 × 2 factorial design, to receive divided dose oral methotrexate every other week versus standard weekly dose methotrexate during the first 6 months of continuation therapy and oral mercaptopurine in a single-dose versus divided dose fashion throughout continuation. Patients on 9201 and 9605 received no anthracyclines, epipodophyllotoxins, alkylating agents or cranial irradiation.…”
Section: Patients and Samplesmentioning
confidence: 99%